Competence and Motivation: Keys to Success for BUMDes Management - Mere, Klemens; Lukitaningtyas, Firina; Sungkawati, Endang (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The performance of BUMDes Management is very important in a business because it is a benchmark for the success of a business. The performance of management is still often ignored by business actors, even though to be able to know the extent of success of a business in carrying out its activities, you must know how these activities are carried out. The successful performance of BUMDes administrators cannot be separated from the competence and motivation of the administrators. This research aims to determine the influence of competence and motivation on the performance of BUMDes administrators in Tajinan District, Malang Regency. The research method uses a quantitative approach. The number of BUMDes in Tajinan District is 12 BUMDes. Each BUMDes has a different number of administrators, a total of 60 administrators. The samples taken in this research were all BUMDes administrators in 12 villages, totaling 60 people. Data collection was carried out by distributing questionnaires. Data analysis uses the t-test (partial test). The research results show that competence and motivation partially influence the performance of BUMDes administrators. Based on the results of this research, it can be recommended that BUMDes in Tajinan District, Malang Regency improve competence by participating in workshops and workshop activities related to BUMDes management. Apart from that, it is hoped that the Village Government will increase work motivation among BUMDes administrators by providing guidance and conducting comparative studies on BUMDes that are capable of managing BUMDes well so that they can improve the economy and standard of living of village communities with the potential that exists in their villages.